Study of Kb X-ray emission spectroscopy applied to Mn(2x)V(1-x)O4 (x=0 and1/3) oxyspinel and comparison with XANES - Ceppi, Sergio Andrés (2014)
Fil: Ceppi, Sergio Andrés. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.